Professoras encarceradas: a educação na prisão de jovens e adultos na perspectiva das professoras que vivenciam o perigo em um ambiente de subjugação e resistência no exercício da docência no presídio de Valença/BA - Vieira, Marcia Cristina Rocha de Sousa (2015)
This Master s research seeks to answer the questions: how did the women teachers who worked in the Conjunto Penal de Valença (CPV) [Valença Prison] develop pedagogic practices in an autonomous way in an environment of subjugation and resistance, using a methodology directed toward the sensitization of values in a space where fear and vulnerability predominate? What were the impediments that they encountered in the teaching exercise in the prison? In this sense, the research of this theme emerged from the time in which I worked as the coordinator of the Federal Program of Literacy Training for Youth and Adults in partnership with the State Government of Bahia, which maintained two groups in the CPV. At that time what caught my attention was the determination of the teachers in confronting the adversities and the impediments in which that education was inserted. Through the narratives which were registered in a prior research, it was possible to identify, in the registers of their voices, the experiences and the knowledge which were significant for their work in teaching in the EJA [Youth and Adult Education] programs in prisons, as well as identify the impediments faced by that education. The research was carried out through the register of oral reports of five teachers who work/worked in the EJA modality in the CPV, through which the data was obtained and analyzed. The authors involved for the theoretical reference are Miguel Arroyo, Paulo Freire, Michael Foucault, Moacir Gadotti, Sérgio Haddad Elionaldo Fernandes Julião, Leôncio José Gomes Soares and Márcia Vieira.